A Multi-Directional Assessment Related To E-Sports As A New Game Experience Field And Socialising Tool - Akkaya, Sümeyra; Sen, Burcu Gezer; Kapıdere, Metin (My University, 2021)
The aim of the research is to examine e-sports as a new game experience and socialization tool from a multidimensional perspective. The case study model, one of the qualitative research methods, was used in the study. The working group of this research consists of 22 teacher candidates studying at İnönü University, Faculty of Education, Department of Primary Education, Primary School Teaching Program in the 2020-2021 academic year. A total of 22 students, 10 males and 12 females, participated in the study. The students were determined by sampling criteria, one of the purposeful sampling methods, among those who have experience in e-sports. Data were collected with a semi-structured interview form developed by the researchers. While creating the form, support was received from 3 field experts. The interview form consisting of 4 open-ended questions prepared by the researcher was used for data collection in this study. The data collected in this study were analyzed by content analysis. According to the findings of the research, it was determined that the teacher candidates define e-sports as online participation-based digital games that require more internet use. While some of the teacher candidates' expressed the view that e-sports socialized, others argued that digital games cause screen addiction and disconnect the individual from sociality.
Keywords: E-sports; Teacher candidates